Tales from the Crypt : Can you fear me now? - Kleid, Neil (New York : Papercut, 2007)
Presents four horror stories in graphic novel format, including a tale about a loser who would sacrifice anything to appear on--and win--the television show "Popstar Idol."
Keywords: Horror -- Comics -- Graphic Novel